Stepping into social waters : photography performed as moving image : an extended essay presented in partial fulfilment of the requirements for the postgraduate degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Mechen, Johanna (Massey University, 2014)
Stepping into Social Waters: A Video Essay on the Waiwhetu Stream, is a photographically derived micro history - an imaginative weaving of moving image - of fact and fiction, which begins with the story of a group of volunteers working in the Waiwhetu Stream. A practice in parallel is created and described by the photographer, a visual mining of a site is undertaken. Ecological and cultural injustices are excavated along with collective historical memory. There is collecting and filming of found stream refuse and reconstructing and re-staging of discarded objects that only exist in story form. The instructional and indexical framework of the project borrows from the greater field of social sciences, visual and material culture, anthropology and archaeology. Cataloguing, numbering, photographing and plotting on a map. Stories are extracted from stream volunteers and local residents, some anecdotal and some archival or historical; these along with the objects found, dictate what is re-staged and re-presented - in a way which is at times uneasy and deliberately plays with the slipperiness of photographic truth and fiction. The photographer transitions the evidential research performativity, by way of selective re-enactment into the Video Essay. A metaphorical and poetic version of that process is described, edited and presented. My studio submission, Stepping into Social Waters: a Video Essay on the Waiwhetu Stream; a 21 minute moving image work, is the culmination of a year's dialogue with a stream and with those connected to it.
Keywords: Video art; Waiwhetu stream; Documentary video; Experimental video; Photography